The Relationship Between Stress Levels and Academic Performance of Undergraduate Nursing Students in the 2024/2025 Academic Year at Universitas Advent Indonesia - Gea, Inesti Febrianti; Boyoh, Debilly Yuan (Jurnal Biologi Tropis, 2025)
Academic stress is one of the psychological factors often experienced by students during higher education. Task pressure, academic demands, and adaptation to the learning environment can affect students' emotional well-being and academic performance. This condition needs to be studied because uncontrolled stress can reduce motivation and concentration in learning. The purpose of this study was to determine the relationship between stress levels and the academic performance of undergraduate nursing students in the 2024/2025 academic year at Advent University Indonesia. This study used a quantitative method with a correlational analytical design and a cross-sectional approach. The sample consisted of 77 students selected using purposive sampling. The research instrument used the Perceived Stress Scale (PSS-10) questionnaire to measure stress levels, while academic performance data was obtained from the Grade Point Average (GPA). The results of the Pearson correlation test showed a significance value of 0.479 and a correlation coefficient of -0.082, which means that there is no significant relationship between stress levels and academic performance. Thus, it can be concluded that stress is not the only factor that affects student learning achievement, as other factors such as motivation, social support, and the academic environment also play a role. The conclusion is that there is no relationship between stress levels and student academic achievement.